Effect of Combined Oral Contrraceptive Pills on Serum Total Cholesterol and Body Mass Index in Females of Reproductive Age Group - Uzma Faryal, Madeeha Jadoon, Sofia Shoukat, Angbeen Ahmad, Shazia Rashid, Rifat Shaheen (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: to find out the effect of combined oral pills on serum total cholesterol as well as Body mass Index (BMI) in two groups: females who were not using any method of hormonal contraceptives (controls) and the subjects using combined oral contraceptive pills in their reproductive age (15-49yrs) Material and Methods: This study was created and executed for this goal at Hazara University in Mansehra. Two groups of 200 married, fertile women who were not pregnant or nursing were created: Group 1 consisted of controls (females who did not use any hormonal contraception), and Group 2 consisted of participants taking combination oral tablets (COCs). The laboratory derived variables studied was serum total cholesterol. BMI was calculated. It was decided to use a 5% level of significance (p0.05). With the help of Pearson’s correlation coefficient r, the relation was established. Results: Serum total cholesterol showed a statistically significant difference. BMI and serum TC did not statistically associate with one another. BMI and serum total cholesterol were positively connected in group 1 and negatively correlated in group 2, respectively. Conclusion: This study facilitated to find out a simple and save method for an efficient and reliable mode of hormonal contraception for practice by general population Keywords: Hormonal contraception, combined oral pills, serum total cholesterol